Study on the evolution of regional future drought-flood abrupt alternation events - Yanqi Wei; Haichao Li; Yuliang Zhou; Nii Amarquaye Commey; Juliang Jin; Ping Zhou (Journal of Hydrology: Regional Studies)
Study region: Bengbu City, situated on the transition zone between southern and northern China. Study focus: Drought-flood abrupt alternation (DFAA) refers to the rapid succession of droughts and floods, including drought-to-flood (DTF) and flood-to-drought (FTD) events. These events occur suddenly and have widespread impacts, making their identification and estimation crucial for enhancing disaster prevention capabilities. This study developed an optimized DFAA index (GDFAI). By combining historical data and General Circulation Models (GCMs), this study analyzed the historical evolution of DFAA events and projected potential risks under future emission scenarios (RCP4.5, RCP8.5, SSP2–4.5, and SSP5–8.5). New hydrological insights: (1) The GDFAI can accurately identify DFAA events with a combined error and miss rate of only 1.24 %; (2) The FTD events were more frequent during the non-flood season, whereas DTF events were concentrated in the flood season; (3) Future projections (RCP4.5, RCP8.5, SSP2–4.5, and SSP5–8.5) showed a slight increase in slight FTD and DTF events outside the flood season. Additionally, June is projected to become a new dual-risk month, while the risk trend of February is estimated to shift from DTF to FTD. These findings can provide scientific references for optimizing reservoir management, agricultural irrigation, and disaster preparedness strategies.